Determination of transverse slope of the runway is paved in view of dynamic phenomena hidrohlisuvannya aircraft - Золотоперий, В.М.; Шинкарьов, Д.Є. (Proceedings of National Aviation University (archive), 2006)
An engineering method is offered and calculations are executed on a ground minimum of possible paved runway’s crossfalls for different classes of the civil airdromes and for the different rain shower zones. The recommendations for planning paved runway’s cross direction profiles and taking special measures for prevention of airplane’s wheels dynamic hydrogliding have been formulated.